PENERAPAN METODE FISHBOWL DISCUSSION UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS VIII B Di MTS AL HIDAYAH BONDOWOSO TAHUN AJARAN 2023/2024 - Nasifah; Moh. Sutomo (Institut Agama Islam Negeri Ponorogo, 2025)
Based on the results of research conducted by researchers, social studies teachers at MTs Al Hidayah Bondowoso still use conventional methods, namely lectures and assignments using whiteboards, which means that the use of this method focuses on teacher and student activity which is less than optimal and students who tend to be passive. The problem in this research is that student learning outcomes are less than the maximum KKM score because the learning methods used by teachers tend to be monotonous, making students easily bored and not listening to the material well. The problem in this research is whether the fishbowl discussion method is effective in improving social studies learning outcomes for class VIII B at MTs Al Hidayah Bondowoso in the 2023/2024 academic year? The aim to be achieved in the research is to identify whether using the fishbowl discussion method is effective or not in improving social studies learning outcomes for class VIII B at MTs Al Hidayah Bondowoso for the 2023/2024 academic year. This research uses Classroom Action Research using the Kemmis and Mc Taggart model using an Action research approach which is carried out in 3 cycles and in each cycle there are two meetings. Each cycle includes the stages of planning, action, observation and reflection. This research uses test results, observation and implementation as instruments in data collection. The application of the fishbowl discussion method is effective in improving learning outcomes. Researchers made improvements in cycle III by applying the fishbowl discussion method and adding games during learning to make students more active and enthusiastic in learning. This is shown by the increase in observation results and documentation of student learning outcomes in cycle III, the percentage of student observations has increased by 92.5%, while student learning outcomes have reached a completeness score of 88.2% Keywords: Fishbowl Discussion Method, Learning Results, Social Sciences